Indigenous cultural competence: A dental faculty curriculum review. (30th December 2017) - Forsyth, C.; Irving, M.; Tennant, M.; Short, S.; Gilroy, J.
Abstract: Background: Indigenous Australians have more than double the rate of poor oral health than their non‐Indigenous counterparts. Cultural competence of dental and oral health practitioners is fundamental to health care and quality of life in addressing health disparities in minority cultural groups in Australia. Higher education curricula reviews have identified the need for institutions to incorporate Indigenous culture and knowledge more widely into the curricula to improve educational outcomes for Indigenous Australians and to increase cultural competence for all students. Aim: The aim of this research was to provide a baseline analysis of Indigenous cultural competence curricula practices to ascertain changes required within Faculty of Dentistry programmes at the University of Sydney to enable students to become more culturally competent upon graduation. Methods: Staff and students of the Doctor of Dental Medicine and Bachelor of Oral Health programmes at the Faculty of Dentistry, University of Sydney participated in an online survey. Quantitative analysis of the survey data was conducted using integrated research electronic data capture survey tools, with open‐ended questions being coded to common responses for those questions. Results: A total of 69 staff (71%) and 191 students (51%) participated in the online survey. The majority of participants perceived there was limited Indigenous content in the curriculum. Most participants reported that Indigenous curriculum was integrated into several units of study. The main pedagogical method for curriculum delivery was lectures, followed by case studies and group discussions. Conclusion: Although some Indigenous content exists in dental faculty curriculum, in‐depth investigation is required to develop a comprehensive, evidenced‐based Indigenous cultural competence teaching framework, for integration into Doctor of Dental Medicine and Bachelor of Oral Health curricula.